If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + g) = -4(g + 1) (3 * 2 + g * 2) = -4(g + 1) (6 + 2g) = -4(g + 1) Reorder the terms: 6 + 2g = -4(1 + g) 6 + 2g = (1 * -4 + g * -4) 6 + 2g = (-4 + -4g) Solving 6 + 2g = -4 + -4g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '4g' to each side of the equation. 6 + 2g + 4g = -4 + -4g + 4g Combine like terms: 2g + 4g = 6g 6 + 6g = -4 + -4g + 4g Combine like terms: -4g + 4g = 0 6 + 6g = -4 + 0 6 + 6g = -4 Add '-6' to each side of the equation. 6 + -6 + 6g = -4 + -6 Combine like terms: 6 + -6 = 0 0 + 6g = -4 + -6 6g = -4 + -6 Combine like terms: -4 + -6 = -10 6g = -10 Divide each side by '6'. g = -1.666666667 Simplifying g = -1.666666667
| -8=-2(8x+5)-5(1-3x) | | 4+5x=7x-15 | | y=-x+14x-24 | | 3x+19+4x-2=180 | | 7+19m=35+12m | | 7.3+5.7=2x+4.7-1x | | 10r^3+40r=0 | | 7y=x+28 | | 8v^3-200v=0 | | 25t+5=25t | | 20+4x=44x | | 8(x-8)+6=-3x+8 | | 25t+5=25 | | -129-8x=10x-15 | | 112000-126000= | | 5x-33+6x+4=180 | | 3E-15+0.1234=0 | | (-0.1)(-0.6)+(-0.1)-(-0.6)= | | y=3E-15 | | x-81=75-5x | | x^2+3kx+k=0 | | 2x+3x-26=180 | | p-15=3 | | 6.2+3.5n=3(0.5n+2.4) | | ln(3-8y)=x | | 4x+136=12x-8 | | 25x^4+25x^3+100x^2+25x+50=0 | | 6(5x-4)=-2x+3 | | x^2-19x=-48 | | 12y+21=9t | | 0=3x^2+4x+2 | | 5x+13=-93-10x |